SYNTHESIS OF CELLULOSE AEROGEL FROM KAPOK FIBER FOR CLEANING THE WASTE OF LUBRICANT OIL - Susilowati, Titi; Muljani, Srie (Jurnal Teknik Kimia, 2020)
Cellulose aerogel is known to be superior in removal of oil pollutants and organic solvent. This research developed the synthesis of cellulose aerogel from kapok fiber, application as an adsorbent for lubricating oil waste and its reusability. Chemical delignification was carried out by immersing the kapok fibers in NaOH 6% solution at 100oC for 1h to obtained a cellulose of 65.5% (SNI-2009). The effect of urea concentration on adsorbent products was studied in the range of 8-16w%. Whereas the effect of cellulose was studied at a concentration range of 0.5-1.5w%. The gelation stage was carried out by adding cellulose in a NaOH/urea solution accompanied by stirring (1000rpm) for 15minutes. The mixture was cooled at 0 oC for 48h to form a gel.  The formed gel is dried by the freeze drying method at -45°C. The cellulose aerogel from kapok fiber with a density of 0.11g/cm3 and porosity of 92.46% had an absorption capacity of up to 11.987g/g in the first cycle. The use of each aerogel cellulose sample to absorb lubricant oil waste reached a maximum of three cycles.  DOI : https://doi.org/10.33005/jurnal_tekkim.v15i1.2305